Formulation of ice size to improve storage and fish quality catches by fisherman - Putra, Fauzi Syah; Putri, Aprilia Syah; Sitepu, Mestiria Harbani (Arwana: Jurnal Ilmiah Program Studi Perairan, 2024)
Indonesia's fisheries export production has large contribution to the world's fish consumption, however, the size of fish export production is inversely proportional to the low cost of export sales. 'The low selling value of fish from Indonesia, because Indonesia fish has low quality. The aim of this research is; (1) knowing the ice size formulation to improve storage quality and quality of caught fish. And (2) understand when the freshness and quality of caught fish decreases. This research was carried out for 1 month starting from September to October 2022. This research used an experimental design. Ice Formulation Experiment was divided into 3 test formulations size, with diameters of 1-5 cm, 6 -10 cm, and 11-15 cm. Addition of ice periodically 6 -12 hours, and changes in ice size are carried out every 1x24 hours starting from the smallest size to the largest in formulation. Fish quality testing is carried out after storage for 3 x 24 hours to measure the best ice size combination formulation. Based on the graph of organoleptic and ALT test results, it shows the best ice formulation is found in sample 1, but in testing using ANOVA the results are not significantly different.